Baseline plasma total homocysteine and adenoma recurrence: results from a double blind randomized clinical trial of aspirin and folate supplementation - Levine, A. Joan (2010)
BACKGROUND: Elevated plasma total homocysteine (tHcy) is an accepted marker of functional folate deficiency but may have independent effects on colorectal neoplasia risk. It is uncertain whether plasma tHcy is associated with risk at the low levels common in a folate-fortified population. METHODS: Study subjects, about half of which were recruited after fortification of grain products with folic acid in the US and Canada, were 871 individuals with a recent history of one or more colorectal adenomas who were randomized to receive either a 1 mg/day folic acid supplement or a placebo within one of three randomly assigned aspirin treatment groups (placebo, 81 or 325 mg/d). Non-fasting plasma tHcy was determined by a GC-MS method. We estimated adjusted risk ratios and 95% confidence intervals for one or more adenoma recurrences for each quartile of baseline plasma tHcy using generalized linear regression with an overdispersed poisson approximation to the binomial. RESULTS: The Q4/Q1 adjusted RR for any adenoma was 0.98; 95% CI 0.70-1.38, p-trend =0.17 in the placebo group, and 0.81; 95% CI 0.58-1.12, p-trend=0.17 in the folic acid group. Results were similar for adenomas with advanced features. There was no modification by sex, aspirin treatment group or MTHFR 677C>T genotype. CONCLUSIONS: Plasma tHcy is not an independent marker for an increase in colorectal adenoma recurrence risk in post-fortification populations where plasma tHcy levels are in the lower range of values. IMPACT: Controlling plasma tHcy levels is unlikely to favorably modify adenoma recurrence risk in folate fortified populations.